ĐKXĐ x khac -1\(A=\frac{x^3+2x^2-1}{x^3+2x^2+2x+1}=\frac{x^3+x^2+x^2+x-x-1}{x^3+x^2+x^2+x+x+1}=\frac{x^2\left(x+1\right)+x\left(x+1\right)-\left(x+1\right)}{x^2\left(x+1\right)+x\left(x+1\right)+\left(x+1\right)}=\frac{\left(x+1\right)\left(x^2+x-1\right)}{\left(x+1\right)\left(x^2+x+1\right)}=\frac{x^2+x-1}{x^2+x+1}\)
\(ta.coA=\frac{x^2+x-1}{x^2+x+1}=\frac{x^2+x+1-2}{x^2+x+1}=1-\frac{2}{x^2+x+1}\)
Để A \(\in Z\Leftrightarrow\frac{2}{x^2+x+1}\in Z\Rightarrow x^2+x+1\inƯ\left(2\right)\Rightarrow\left(x+\frac{1}{2}\right)^2+\frac{3}{4}\in\left\{\pm1;\pm2\right\}\)
giải ra ta được \(x=0,x=-1\)(t/m)
Đúng 0
Bình luận (0)